2015
DOI: 10.1039/c5nr02898a
|View full text |Cite
|
Sign up to set email alerts
|

A galactose-functionalized dendritic siRNA-nanovector to potentiate hepatitis C inhibition in liver cells

Abstract: A RNAi based antiviral strategy holds the promise to impede hepatitis C viral (HCV) infection overcoming the problem of emergence of drug resistant variants, usually encountered in the interferon free direct-acting antiviral therapy. Targeted delivery of siRNA helps minimize adverse 'off-target' effects and maximize the efficacy of therapeutic response. Herein, we report the delivery of siRNA against the conserved 5'-untranslated region (UTR) of HCV RNA using a liver-targeted dendritic nano-vector functionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Immunological assays indicated that the immunogenicity of the conjugated HBsAg was enhanced when compared to HBsAg alone [ 182 ]. Lakshminarayanan reported liver-targeted dendritic nano-vector functionalized with a galactopyranoside ligand for the delivery of siRNA [ 161 ] ( Table 2 ). Targeted delivery of siRNA to the liver was achieved via a highly specific ligand—receptor interaction between dendritic galactose and the asialoglycoprotein receptor.…”
Section: Application Of Dendrimers For the Treatment Of Viral Infementioning
confidence: 99%
See 1 more Smart Citation
“…Immunological assays indicated that the immunogenicity of the conjugated HBsAg was enhanced when compared to HBsAg alone [ 182 ]. Lakshminarayanan reported liver-targeted dendritic nano-vector functionalized with a galactopyranoside ligand for the delivery of siRNA [ 161 ] ( Table 2 ). Targeted delivery of siRNA to the liver was achieved via a highly specific ligand—receptor interaction between dendritic galactose and the asialoglycoprotein receptor.…”
Section: Application Of Dendrimers For the Treatment Of Viral Infementioning
confidence: 99%
“…A decrease in HCV RNA levels of 75% was achieved in HCV-JFH1 infectious cell culture systems. The targeted release mechanism of the formulation revealed it is a potential therapeutic for the treatment of infections in the liver such as hepatitis [ 161 ].…”
Section: Application Of Dendrimers For the Treatment Of Viral Infementioning
confidence: 99%
“…siRNA encounters some problems including low cellular uptake, rapid degradation by nucleases as well as inadequate blood stability [56], so many studies have used nanoparticles to solve these problems and to minimize the adverse effect of “off-targeting”. Lakshminarayanan et al used a galactose functionalized dendritic nanovector (DG) as a carrier for siRNA against the 5' untranslated region of the HCV genome [18]. The siRNA-DG formed a stable complex that had target-oriented delivery through the interaction between its free galactose residues and asialoglycoprotein receptor.…”
Section: Nanoparticles As Carrier For Anti-hcv Sirnamentioning
confidence: 99%
“…The delivered siRNA localized in the perinuclear region (the site of HCV replication) in which NS3 and NS5b viral proteins are co-localized. There was a significant inhibition in JFH1 RNA titer, so this new siRNA-DG nanovector is a promising option for HCV therapeutics [18]. …”
Section: Nanoparticles As Carrier For Anti-hcv Sirnamentioning
confidence: 99%
See 1 more Smart Citation